The Reconstruction of White Southern Womanhood, 1865-1895 - Censer, Jane Turner (Book collections on Project MUSE., 2003)
The important but little-known story of elite southern white women's successful quest for a measure of self-reliance and independence between antebellum strictures and the restored patriarchy of Jim Crow.